Предмет: Алгебра,
автор: natulyakim
упростите выражение (-1/(x-4)+16/(x^2-16)+2/(x+4))(x^2-8x+16)
Ответы
Автор ответа:
0
1) (-(x+4)+16)/(x-4)(x+4) = (-x -4 +16)/(x-4)(x+4)=(12-x)/(x-4)(x+4)
2) 2/(x+4)(x²-8x+16) = 2 /(x+ 4)(x-4)²
3) (12-x)(x-4)+2) /(x+4)(x-4)² =(16x-48-x²+2)/(x+4)(x-4)² = (16x-46-x²)/(x+4)(x-4)²
2) 2/(x+4)(x²-8x+16) = 2 /(x+ 4)(x-4)²
3) (12-x)(x-4)+2) /(x+4)(x-4)² =(16x-48-x²+2)/(x+4)(x-4)² = (16x-46-x²)/(x+4)(x-4)²
Похожие вопросы
Предмет: Алгебра,
автор: cartoshka12
Предмет: Алгебра,
автор: AppleGameplays5
Предмет: География,
автор: dilfuzabaktybekova98
Предмет: Математика,
автор: anfisashirokov
Предмет: Биология,
автор: kkotovchihina